(untitled) (E Conference Zone, 2022)
In this paper, using the two-band Kane model, the non-parabolic dispersion of electrons of the velocity of the change in the chemical potential with respect to the temperature of a quasi-two-dimensional electron gas from the chemical potential is analyzed using a two-band Kane model. This does not take into account the processes of electron collisions between themselves and defects, transfer of electrons to local levels or conduction bands in the barrier region due to heat, the influence of the valence band, the influence of an external magnetic field, and other factors. An analytical analysis of the obtained results was carried out. It is shown that the corrections αT at low temperatures, in which the non-parabolicity of the band affects the generating maxima